Amygdala structure and aggressiveness in borderline personality disorder - Mancke, Falk; Herpertz, Sabine; Hirjak, Dusan; Knies, Rebekka; Bertsch, Katja (European archives of psychiatry and clinical neuroscience, 2018)
Aggressiveness is considered an important clinical feature of borderline personality disorder (BPD) and has been associated with alterations of the amygdala. However, studies that analyzed the exact location of amygdala alterations associated with aggressiveness in BPD or that systematically compared female and male BPD patients are missing. In the current study, we therefore investigated a sex-mixed sample of BPD patients and healthy volunteers and applied an automated segmentation method that allows the study of both, alterations of amygdala volume and localized amygdala shape. Volumetric results revealed no difference in amygdala volume between BPD patients and healthy volunteers, but a trend for a positive association between volume of the right amygdala and aggressiveness in male BPD patients. Analyses of amygdala shape showed a trend for a group by sex interaction effect in the left laterobasal amygdala, without a difference in subgroup analyses. Finally, regions of the left superficial and laterobasal amygdala of male BPD patients were positively associated with aggressiveness. In sum, our results emphasize the need to consider sex-specific effects and demonstrate a link between male BPD patients’ aggressiveness and amygdala regions that are particularly related to social information processing and associative emotional learning.